Research on a Model of Enhancing Factors' Effects Based on Trust Evaluation for P2P Network - Zuchang Zhang; Cheng Wang (Dianxin kexue)
In the transaction evaluation mechanism,trust is formed by many kinds of factors,but due to the characteristics of its own,its effects and influences are different.By using the relationship between appropriate,it enhances the effects of some important factors and the role of trade.That can effectively improve the accuracy and validity of the evaluation model.A model of enhancing the factors' effects based on the trust evaluation for P2P network was proposed,a new calculation method of the trust evaluation,and the model's simulation results were given.The experimental results show that the evaluation model has significant effect.